Abnormal Uterine Bleeding Among Rural Adolescent Schoolgirls: A Cross-Sectional Study - Yasir Salih; Ghaday S. Almutairi; Norah H. Alhumaidi; Nadiah Alhabardi; Ishag Adam (Medicina)
Background and Objectives: The International Federation of Gynecology and Obstetrics (FIGO) and the American College of Obstetricians and Gynecologists (ACOG) define abnormal uterine bleeding (AUB) as “bleeding from the uterus that is abnormal in regularity, volume, frequency, or duration and occurs in the absence of pregnancy”. The impact of AUB on the physical and psychosocial well-being of adolescent girls can be significant. In this study, we aim to investigate the menstrual cycle characteristics in adolescent Sudanese schoolgirls and the prevalence of abnormal uterine bleeding (AUB) and its associated factors. Materials and Methods: A school-based cross-sectional study was conducted in Almatamah locality, Sudan. A questionnaire was used to collect sociodemographic data and menstrual cycle parameters. Weight and height were measured, body mass index (BMI) was calculated, and hemoglobin levels were determined. Logistic regression was also performed. Results: Of the 162 girls in the study, 27.2% had frequent cycles, 3.7% had infrequent cycles, 2.5% had prolonged menses duration, 44.4% had irregular cycles, and 21.0% had heavy menstrual bleeding. The overall prevalence of AUB in the study was 64.8%. None of the investigated factors (chronological age, maternal education or occupation, gynecological age, BMI, and hemoglobin level) were associated with AUB. Conclusions: In conclusion, the prevalence of AUB was high among the study participants, with irregular cycles, frequent cycles, and heavy menstrual bleeding being the most common types.